2021
DOI: 10.1080/2162402x.2021.1954800
|View full text |Cite
|
Sign up to set email alerts
|

In vitro OP9-DL1 co-culture and subsequent maturation in the presence of IL-21 generates tumor antigen-specific T cells with a favorable less-differentiated phenotype and enhanced functionality

Abstract: T cell receptor (TCR)-redirected T cells target intracellular antigens such as Wilms' tumor 1 (WT1), a tumorassociated antigen overexpressed in several malignancies, including acute myeloid leukemia (AML). For both chimeric antigen receptor (CAR)-and TCR-redirected T cells, several clinical studies indicate that T cell subsets with a less-differentiated phenotype (e.g. stem cell memory T cells, T SCM ) survive longer and mediate superior anti-tumor effects in vivo as opposed to more terminally differentiated T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Therefore IL-21 or IL-15 were commonly administrated during manufacturing. Indeed, several studies reported that the addition of IL-21 or IL-15 results in increased proportion of CAR-T SCM and T CM (including WT1-and CD19-CAR-T cells) associated with enhanced persistence and anti-tumor effects (85,(136)(137)(138)(139)(140). Furthermore, induced secretion of IL-21 by CD19-CAR-T cells can even maintain CAR-T cells in early memory phenotype and enhance anti-tumor activity in vivo, which was already demonstrated in mice transplanted with Ramos B cells (139).…”
Section: Conferring Stemness On Car-t Cellsmentioning
confidence: 99%
“…Therefore IL-21 or IL-15 were commonly administrated during manufacturing. Indeed, several studies reported that the addition of IL-21 or IL-15 results in increased proportion of CAR-T SCM and T CM (including WT1-and CD19-CAR-T cells) associated with enhanced persistence and anti-tumor effects (85,(136)(137)(138)(139)(140). Furthermore, induced secretion of IL-21 by CD19-CAR-T cells can even maintain CAR-T cells in early memory phenotype and enhance anti-tumor activity in vivo, which was already demonstrated in mice transplanted with Ramos B cells (139).…”
Section: Conferring Stemness On Car-t Cellsmentioning
confidence: 99%